Reading Interest and Teacher’s Efforts in Increasing Reading Interest for Elementary Schools - Maryatiningsih, Ria Rizky; Abduh, Muhammad (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
Interest in reading is one aspect that is the progress of the nation and state. Reading provides a cognitive experience that can stimulate the mind. The research was conducted at Mangkubumen Kidul Elementary School No.16 Laweyan District, Surakarta City. The purpose of the research conducted by researchers is to analyze the efforts made by teachers to increase students' reading interest. The research method used by researchers is qualitative research method with a case study approach. Data collection methods used are observation, interviews and documentation. The research subjects included school principals, teachers and students in class II and class V. The object of the study was the teacher's efforts to increase students' interest in reading at Mangkubumen Kidul Elementary School No. 16. The data validity technique used is data triangulation. Data analysis used is data reduction, data presentation and conclusion. The results and research findings include teachers having strategies by motivating students always read and creating an academic and literative environment. The obstacle experienced is the competition between reading books and current gadgets which greatly influences students to have a good character of interest in reading.